Effects of nutrient omission on growth and nutritional status of crambe (Crambe abyssinica) plants in eastern Amazon - Sousa, Karen Sabrina de Brito; Viegas, Ismael de Jesus Matos; Alves, Jose Darlon Nascimento; Conceiao, Heraclito Eugenio Oliveira da; Silva, Bianca Cavalcante da [UNESP]; Silva, Dioclea Almeida Seabra; Oliveira, Jairo Neves de [UNESP]; Okumura, Ricardo Shigueru; Rodrigues, Dagila Melo (Southern Cross Publishing, 2024)
The objective of this study was to assess the impact of nutrient omission and liming on the growth and nutritional status of crambe (Crambe abyssinica Hochst) plants in the eastern Amazon region of Brazil. The experiment was conducted in a greenhouse at the Federal Rural University of the Amazon, Campus Capitao Pogo, Para, Brazil. The experimental design was a completely randomized block with 11 treatments and five repetitions. The treatments were as follows: control without lime, control with lime, complete with lime, nitrogen (N) omission with lime, phosphorus (P) omission with lime, potassium (K) omission with lime, calcium (Ca) omission without lime, magnesium (Mg) omission without lime, sulfur (S) omission with lime, boron (B) omission with lime, and zinc (Zn) omission with lime. Following a 60-day period of cultivation, an evaluation was conducted on the biometric variables, biomass production, nutrient concentration, and the presence of symptoms indicative of nutrient deficiencies (N, P, K, Ca, Mg, S, B, and Zn). The experimental data indicated that the omission of nutrients had a deleterious effect on the biometric variables in comparison to the complete treatment with lime. The control treatments with and without the addition of lime, as well as the treatment with P omission with lime, exhibited the most restricted plant growth, with plant height measuring less than 7.0 cm and the number of leaves lower than 3.5. The plants exhibited deficiency symptoms indicative of deficiencies in their development. The most pronounced severe symptoms were observed in the treatments involving P omission with lime and in both controls with and without lime. These findings highlight the necessity of applying lime to the soil in crambe crops and underscore that P is the most limiting nutrient for this crop.
Keywords: mineral nutrition; oilseed; plant production